CASH FLOW ANALYSIS AS A PLANNING AND CONTROL TOOL IN PT. BERMA KARYA BERSAMA - Siti Junaida Hasibuan; Richna Handriyani (Jurnal Ekonomi, 2023)
This study aims to determine the cash flow statement (cash flow) as a planning and control tool by using the cash flow ratio of PT. Berma Karya Bersama. This type of research is qualitative research that is descriptive in nature. Results and discussion of this research Cash flow management by PT. Berma Karya Bersama has not been effective and efficient, where it does not create separate accounts for company and personal funds, does not separate incoming and outgoing cash accounts, and every expenditure or small transaction that is carried out every day with cash does not keep records of expenses. After analyzing the company's cash flow, it can be seen that the cash flow of PT. Berma Karya Bersama during the 2017-2019 period experienced ups and downs. It can be seen that the net cash received from the company's operating activities is able to offset the payment of obligations and also the condition of operating cash flows can be offset by activities originating from investing and financing.